Matrine regulates autophagy in ileal epithelial cells in a porcine circovirus type 2-infected murine model - Wang, Hong; Sun, Na; Sun, Panpan; Zhang, Hua; Yin, Wei; Zheng, Xiaozhong; Fan, Kuohai; Sun, Yaogui; Li, Hongquan (Frontiers in Microbiology, 2024)
Introduction: Porcine circovirus type 2 (PCV2) is an important pathogen that causes diarrhea in nursery and fattening pigs, resulting in huge economic losses for commercial pig farms. Protective efficacy of vaccines is compromised by mutations in pathogens. There is an urgent need to articulate the mechanism by which PCV2 destroys the host's intestinal mucosal barrier and to find effective therapeutic drugs. Increasing attention has been paid to the natural antiviral compounds extracted from traditional Chinese medicines. In the present study, we investigated the role of Matrine in mitigating PCV2-induced intestinal damage and enhancing autophagy as a potential therapeutic strategy in mice. Methods: A total of 40 female, specific-pathogen-free-grade Kunming mice were randomly divided into four groups with 10 mice in each group: control, PCV2 infection, Matrine treatment (40 mg/kg Matrine), and Ribavirin treatment (40 mg/kg Ribavirin). Except for the control group, all mice were injected intraperitoneally with 0.5 mL 10 5.4 50% tissue culture infectious dose (TCID50)/mL PCV2. Results: While attenuating PCV2-induced downregulation of ZO-1 and occludin and restoring intestinal barrier function in a PCV2 Kunming mouse model, treatment with Matrine (40 mg/kg) attenuated ultrastructural damage and improved intestinal morphology. Mechanistically, Matrine reversed PCV2-induced autophagosome accumulation by inhibiting signal transducer and activator of transcription 3 (STAT3) phosphorylation and upregulating Beclin1 protein expression, thus resisting viral hijacking of enterocyte autophagy. Discussion: Our findings demonstrate that Matrine may be a novel, potential antiviral agent against PCV2 by activating intestine cellular autophagy, which provides a new strategy for host-directed drug discovery.